From burnout to engagement: enhancing the wellbeing and performance of conservationists - Loffeld, Thirza A. C.; Black, Simon A.; Humle, Tatyana (Frontiers in Veterinary Science, 2025)
The purpose of this study was to explore how job characteristics relate to multiple dimensions of work performance in conservation professionals, with burnout and work engagement as mediating factors. A global sample of 561 conservation professionals across 98 countries completed an online survey. Using the Job Demands-Resources (JD-R) model and structural equation modelling, we found that participants with more frequent access to job resources (e.g., autonomy in work methods, social support at work, and availability of useful information), reported higher levels of work engagement. In turn, greater work engagement, characterised by vigour, dedication and absorption, was associated with increased task performance (e.g., working efficiently, managing time effectively) and contextual performance (e.g., taking initiative, creative problem-solving). Contrary to previous research in other sectors, job demands did not show a direct relationship to burnout in this conservation sample. However, higher burnout was linked to lower task performance. Moreover, burnout mediated the relationship between job resources and task performance: greater job resources were associated with lower levels of burnout, which in turn was associated with higher task performance. Our findings underscore the importance for both individual professionals and conservation organisations to enhance job resources and work engagement, given their positive relationships with multiple work performance indicators. These results may guide efforts to identify which perceived job characteristics are most likely to enhance performance, either directly or indirectly, through increased work engagement or reduced burnout. Furthermore, when organisations observe a decline across various performance indicators, this may signal a need to strengthen support for staff wellbeing and motivation. This study is the first to quantitatively examine relationships between job characteristics and multiple dimensions of work performance in a global sample of conservation professionals, highlighting the JD-R model’s relevance to conservation.